New Oxazaborolidine Catalysts for the Diels–Alder Reaction - Shimoda, Yasushi; Yamamoto, Hisashi (Synthesis, 2017)
A new axially chiral oxazaborolidine catalyst has been developed. This catalyst consists of a chiral boronic acid and an easily modifiable achiral amino alcohol. It could be applied to a Diels–Alder reaction to give the corresponding adduct with good enantioselectivity. Additionally, the bis(oxazaborolidine) catalyst, bearing two Lewis acidic centers enabled a Diels–Alder reaction with higher enantioselectivity.
Keywords: Diels–Alder reaction; boronic acids; Lewis acid; asymmetric synthesis; oxazaborolidines